ONE EVALUATION METHOD FOR THE CONTRIBUTION OF SUBSTRUCTURE STIFFNESS TO ARRAY FRAMEWORK STIFFNESS (MT) - WANG Chao; SUN XiaoGang; GU YeQing; Lü ZhenHua; Lü YiNing (Jixie qiangdu)
Stiffness performance is an important index to evaluate the bearing capacity of array framework and radar working accuracy. The mean square root of reflector deformation is often used to measure the stiffness performance of array, but the root mean square method can only analyze the overall stiffness of the framework, and can not evaluate the stiffness of local modules and their contribution to the overall stiffness.To solve this problem, the stiffness contribution of substructure（λ） and substructure bearing coefficient（α） were proposed based on the design criteria of substructure strain energy and uniform strain energy density, which has high calculation efficiency and wide application. Through this two parameters, the stiffness contribution of substructure in complex structure can be evaluated and analyzed conveniently. Finally, taking a typical vehicle mounted phased array radar as an example, the contribution and matching of the box girder substructure and T type joint substructure to the array framework were analyzed detailly, and then the influence of the array panel on the substructure stiffness contribution of the frame was analyzed. Through the analysis, some improvement design suggestions were put forward for the lightweight and bearing capacity design of the array antenna frame.